ナンキョク ジョウクウ ノ セイソウケン タイキ サイシュ ヨウ グラブサンプリング ソウチ ノ カイハツ - 本田, 秀乍; ホンダ, ヒデユキ; 森本, 真司; モリモト, シンジ; 秋山, 弘光; アキヤマ, ヒロミツ; 橋田, 元; ハシダ, ゲン; 青木, 周司; アオキ, シュウジ; 宇井, 啓高; ウイ, ヒロタカ; et al. (1996)
P(論文) 南極上空の成層圏大気の各種微量成分やそれらの同位体比を測定するために, 簡単なグラブサンプリング装置を新たに開発した。この装置の打ち上げにはゴム気球を用い, 厳しい実験条件下でも小人数で放球作業が可能となるように設計した。大気試料の汚染防止と取り扱いの簡素化には特に配慮した。サンプリング装置の主要構成部は, 電磁弁と手動弁付きの15リットル試料容器, 試料採取の実行・装置の位置および各種動作状況データの伝送用制御装置, 電池, 送信機である。これらすべてを, 着地時の緩衝装置付きのアルミフレーム製ゴンドラ内に組み込んだ。またゴンドラなどからの汚染がない大気を直接的に採取するために, 試料採取時にはゴンドラ全体を上下反転し, その後元の位置に戻す機構を取り付けた。実験では, さらに飛翔位置追跡用のGPS受信機とレーウィンゾンデを装備した。装置の総重量は約11kgであった。実際の観測には, 位置情報および各種動作状況データのクイックルック表示用処理装置を用意した。さらに, ゴム気球へのヘリウムガス充填を簡単にするため, 新しいガス充填システムも開発した。1996年1月22日と25日に昭和基地で計3機のグラブサンプリング装置を放球し, 基地付近の海氷上で回収することによって, この装置の所期の性能を確認した。 In order to measure the concentrations of various minor constituents and their isotopic ratios in the stratosphere over Antarctica, a simple grab sampling system was newly developed. The sampling system was designed to be launched by a small number of personnel using a rubber balloon under severe experimental conditions. Special attention was paid to minimize the contamination of sample air, as well as to allow easy handling of the system. The sampler consisted mainly of a 15l sample container with electromagnetic and manual valves, control electronics for executing the air sampling procedures and sending the position and status information of the sampler to the ground station, batteries and a transmitter. All these parts were assembled in an aluminum frame gondola with a shock absorbing system for landing. The sampler was equipped with a turn-over mechanism of the gondola to minimize contamination from the gondola, as well as with a GPS receiver and a rawinsonde for its tracking. Total weight of the sampler was about 11kg. To receive, display and store the position and status data of the sampling system at the ground station, a simple data acquisition system with a portable receiver and a microcomputer was also developed. A new gas handling system was prepared to simplify the injection of He gas into the balloon. For air sampling experiments, three sampling systems were launched at Syowa Station (69°00′S, 39°35′E), Antarctica and then recovered on sea ...